(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In recent years, the Uzbek language has undergone significant transformations in its development and usage in various fields, including science and academia. With the increasing globalization of knowledge and the need for effective communication among scholars worldwide, the usage of linguistic terms in Uzbek language has become a priority. However, the adoption of Western linguistic concepts and terminology has posed challenges in finding equivalent terms in the Uzbek language. As a result, scholars in Uzbekistan often employ alternative versions of linguistic terms in scientific articles, which may have both positive and negative implications. This article aims to explore the use of alternative versions of linguistic terms in Uzbek language in scientific articles and provide a critical analysis of the benefits and drawbacks associated with this practice.